PENYIKSAAN OLEH JUNTA MILITER MYANMAR TERHADAP PARA DEMONSTRAN ANTI KUDETA MENURUT KONVENSI ANTI PENYIKSAAN 1984: Torture By The Myanmar Military Junta Of Anti-Coup Demonstrants According To The 1984 Anti-Torture Convention - Biolanda Latifa; Andrey Sujatmoko (Reformasi Hukum Trisakti, 2024)
Since the coup in 2021, the Myanmar military has been involved in serious acts of violence against demonstrators, raising international concerns. The problem in this research is whether the acts of violence against anti-coup demonstrators by the Myanmar Military Junta can be classified as torture under the 1984 Convention Against Torture and how the resolution of these violence cases can be achieved. The normative research method with literature review and the use of secondary data as research materials is employed. The results of the analysis indicate that the Myanmar Military Junta has committed mass killings, arbitrary detentions, widespread torture of detainees, and political suppression of demonstrators. These practices blatantly violate the provisions of the 1984 Convention Against Torture, which expressly prohibits torture and cruel treatment. Despite Myanmar not ratifying the 1984 Convention Against Torture, the author emphasizes that the Military Junta remains obligated to initiate legal proceedings against the perpetrators of violence, particularly the Tatmadaw personnel. To date, there has been no legal resolution for the violence perpetrated by the military against anti-coup demonstrators, leaving a distressing lack of justice.